2022
DOI: 10.1155/2022/9547413
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Coupled and Coordinated Development between China’s Cross‐border E‐commerce Supply Chain and Economic System

Abstract: This study constructs a coupling model and establishes an index system for the coupled and coordinate development between cross-border e-commerce supply chain system and economic system. The index system adopts supply chain, foreign trade, e-commerce, e-commerce logistics, economic development, social consumption, talent environment, and technological innovation as sequential covariates. The calculation shows that the first three batches of 35 cross-border e-commerce comprehensive pilot areas (CBECCPA in brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Other studies [95][96][97] outline that the impact of the coupling and coordination degree of digital business and digital governance on sustainable development is a multifaceted matter, encompassing diverse and occasionally contentious viewpoints. Proponents [98][99][100] argue that this integration enhances economic efficiency, contributes to innovation, and fosters data-driven decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies [95][96][97] outline that the impact of the coupling and coordination degree of digital business and digital governance on sustainable development is a multifaceted matter, encompassing diverse and occasionally contentious viewpoints. Proponents [98][99][100] argue that this integration enhances economic efficiency, contributes to innovation, and fosters data-driven decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research focusing on this aspect mainly examines how cross-border e-commerce and pilot zones affect regional economic growth, e.g., through which channels and pathways [57][58][59], the extent of this impact [60][61][62], and the degree of heterogeneity [63][64][65]. It is believed that cross-border e-commerce and pilot zones have a positive effect on regional economic growth, mainly via facilitating trade [66], promoting digital economy development [67], cultivating new industry formats [68], and supporting upgrades to the industrial supply chain [69]. Some studies have revealed certain heterogeneities in the impacts of cross-border e-commerce and pilot zones on regional economic growth, particularly in terms of regional distribution [70], city level [60], and the degree of cross-border e-commerce development [71,72].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e e e increases, the degree of ordering of the system increases and then decreases. The degree of ordering of the j S ordinal parametric component ji e is thus defined [25]:…”
Section: System Orderlinessmentioning
confidence: 99%